“Everything Plays a Part Doesn’t It?’’: A Contemporary Model of Lifelong Coach Development in Elite Sport - Pete Holmes; Richard L. Light; Andrew C. Sparkes (Education Sciences, 2025)
Coach development is typically considered to consist of a complex mix of experiences, including formal, informal and non-formal. Elements of the early research in this area led to the production of a model of long-term coach development (LTCD) over a decade ago, consisting of three core categories of experience: athletic, coaching and education, later published in a number of significant coaching documents. Whilst this model has clearly been of benefit in providing a framework to consider long-term coach development, it can also be considered to have its limitations in focusing on a somewhat narrow coaching context (typically Olympic sports in North America) and lacking currency. This study therefore attempted to consider and update this model to a professional team sport context away from North America by investigating the life stories of head coaches in English rugby league. Data collection consisted of a novel life story approach, whilst analysis utilised elements of constructivist grounded theory. Though supporting elements of the original LTCD model, results here provide an additional category of experience occurring prior to athletic experience, childhood, consisting of a number of sub-themes, alongside several other novel elements with implications for both research and practice. This work points towards a need to further understand coaches’ lifelong developmental journeys across a range of sports and contexts.